ON THE DISTRIBUTION OF MAXIMAL PERCENTAGES IN PÓLYA'S URN. Issue 3 (22nd September 2016) - Nadarajah, Saralees
Abstract : Schulte-Geers and Stadje [ Journal of Applied Probability, 2015, 52: 180–190] gave several closed form expressions for the exact distribution of the all-time maximal percentage in Pólya's urn model. But all these expressions corresponded to an integer parameter taking the value 1. Here, we derive much more general closed form expressions applicable for all possible values of the integer parameter. We also illustrate their computational efficiency.